Injector design space exploration for an ultra-low NOx hydrogen micromix combustion system - Agarwal, Parash; Sun, Xiaoxiao; Gauthier, Pierre Q.; Sethi, Vishal (ASME, 2019)
The depletion of fossil fuel resources, as well as the increasing environmental concerns have become the driving forces towards the research and development necessary for the introduction of alternative fuel such as hydrogen into civil aviation. Hydrogen is a suitable energy source primarily because it is free of carbon and other forms of impurities and is also the most abundant element in the universe. The advantages of using Liquid Hydrogen (LH2) for civil aviation extends beyond carbon-free mission level emissions; LH2 combustion can potentially reduce NOx emission by up to 90%, providing long-term sustainability and unrivalled environmental benefits. The paper presents a simplified parametric analysis to investigate the influence of various injector design parameters on a hydrogen micromix combustor reactive flow field. The main characteristics investigated are the flame structure (shape and position), the aerodynamic stabilization of the flame and the resulting NOx emissions. The design parameters include variations in the air-feed dimensions and the hydrogen injection diameter. A suitable numerical model was established by comparing various turbulence modelling approaches, reaction mechanisms and turbulence-chemistry interaction modelling schemes. The predictive capabilities, and limitations, of each of these modelling approaches, are assessed. The numerical challenges and limitations associated with modelling H2/air combustion at high pressure and temperature conditions are detailed. The influence of varying the injector design parameters on the mixing and hence the NOx characteristics is assessed.
Keywords: Fossil fuels; High pressure (Physics); Energy resources; Computer simulation; Combustion chambers; Chemically reactive flow; Turbulence; Flames; Commercial air transport; Carbon; Emissions; Nitrogen oxides; Hydrogen; Ejectors; Combustion systems